The Impact of Cost Allocation on Key Decisions of Supply Chain Participants - Elena Panfilova; Natalia Dzenzeliuk; Olga Domnina; Natalia Morgunov?; ?lena Zatsarinnaya (International Journal of Supply Chain Management, 2020)
Abstract - Modern business processes are impossible without a logistics system. Logistics costs constitute the lion’s share in the total product cost. The purpose of our research is to study the dependence of decision-making on the level of logistics costs. In order to achieve the goal set, questionnaire, mathematical modeling and analysis methods were used in the study. The main problems of cost management in supply chains were highlighted. In the course of our research, we concluded that a universal solution to the problem can be developed for a limited segment of enterprises, since there is no identical solution to increasing cost efficiency for different types of enterprises. According to the results of the questionnaire, managers’ decisions on increasing efficiency are dependent on their subjective desires rather than dictated by the economic efficiency. Sixty-seven per cent of the respondents are ready to reject a profitable project due to risks. The questionnaire also showed that only 4% of the managers are ready to quit an already implemented project if it is ineffective. This begs the question: do all projects prove to be really effective after their implementation? A two-factor mathematical model with a dummy variable showed the dependence of increased logistics costs on the period in which they were implemented. The mathematical model obtained during the study will be useful for predicting and budgeting the level of logistics costs. It can also encourage independent enterprises to build advanced mathematical models.